Fate of Cajal-Retzius neurons in the postnatal mouse neocortex - Chowdhury, Tara G.; Jimenez, Jessica C.; Bomar, Jamee; Cruz-Martin, Alberto; Cantle, Jeffrey P.; Portera-Cailliau, Carlos (Frontiers in Neuroanatomy, 2010)
Cajal-Retzius (CR) neurons play a critical role in cortical neuronal migration, but their exact fate after the completion of neocortical lamination remains a mystery. Histological evidence has been unable to unequivocally determine whether these cells die or undergo a phenotypic transformation to become resident interneurons of Layer 1 in the adult neocortex. To determine their ultimate fate, we performed chronic in vivo two-photon imaging of identified CR neurons during postnatal development in mice that express the green fluorescent protein (GFP) under the control of the early B-cell factor 2 (Ebf2) promoter. We find that, after birth, virtually all CR neurons in mouse neocortex express Ebf2. Although postnatal CR neurons undergo dramatic morphological transformations, they do not migrate to deeper layers. Instead, their gradual disappearance from the cortex is due to apoptotic death during the second postnatal week. A small fraction of CR neurons present at birth survive into adulthood. We conclude that, in addition to orchestrating cortical layering, a subset of CR neurons must play other roles beyond the third postnatal week.